Antioxidant therapy for infertile couples: a comprehensive review of the current status and consideration of future prospects - Saleh, Ramadan; Sallam, Hassan; Elsuity, Mohamad AlaaEldein; Dutta, Sulagna; Sengupta, Pallav; Nasr, Ahmed (Frontiers in Endocrinology, 2025)
Oxidative stress (OS) is established as a key factor in the etiology of both male and female infertility, arising from an imbalance between reactive oxygen species (ROS) production and the endogenous antioxidant (AOX) defenses. In men, OS adversely affects sperm function by inducing DNA damage, reducing motility, significantly impairing sperm vitality through plasma membrane peroxidation and loss of membrane integrity, and ultimately compromising overall sperm quality. In women, OS is implicated in various reproductive disorders, including polycystic ovary syndrome, endometriosis, and premature ovarian failure, leading to diminished oocyte quality, disrupted folliculogenesis, and poorer reproductive outcomes. Antioxidant therapy represents a promising intervention to mitigate the harmful effects of ROS on reproductive health in additions to its easy accessibility, safety, and low cost. Despite several findings suggesting improvements in fertility potential with AOX therapy, the data remains inconclusive regarding optimal dosage and combination, duration of treatment, and the specific patient populations most likely to benefit. In this review, we discuss the role of AOXs in the management of infertile couples, focusing on their biological mechanisms, potential adverse effects, therapeutic efficacy, and clinical applications in improving reproductive outcomes in both natural conception and medically assisted reproduction. Additionally, we highlight the current practice patterns and recommendations for AOX supplementation during the course of infertility treatment. Further, we provide an overview on the limitations of the current research on the topic and insights for future studies to establish standardized AOX regimens and to assess their long-term impact on key outcomes such as live birth rates and miscarriage rates.